Menaquinone‐4 enhances osteogenic potential of human amniotic fluid mesenchymal stem cells cultured in 2D and 3D dynamic culture systems. (31st August 2017) - Mandatori, Domitilla; Penolazzi, Letizia; Pipino, Caterina; Di Tomo, Pamela; Di Silvestre, Sara; Di Pietro, Natalia; Trevisani, Sara; Angelozzi, Marco; Ucci, Mariangela; Piva, Roberta; Pandolfi, Assunta
Abstract: Menaquinones, also known as Vitamin K2 family, regulate calcium homeostasis in a 'bone‐vascular cross‐talk' and recently received particular attention for their positive effect on bone formation. Given that the correlation between menaquinones and bone metabolism to date is still unclear, the objective of our study was to investigate the possible role of menaquinone‐4 (MK‐4), an isoform of the menaquinones family, in the modulation of osteogenesis. For this reason, we used a model of human amniotic fluid mesenchymal stem cells (hAFMSCs) cultured both in two‐dimensional (2D) and three‐dimensional (3D; RCCS™bioreactor) in vitro culture systems. Furthermore, to mimic the 'bone remodelling unit' in vitro, hAFMSCs were co‐cultured in the 3D system with human monocyte cells (hMCs) as osteoclast precursors. The results showed that in a conventional 2D culture system, hAFMSCs were responsive to the MK‐4, which significantly improved the osteogenic process through γ‐glutamyl carboxylase‐dependent pathway. The same results were obtained in the 3D dynamic system where MK‐4 treatment supported the osteoblast‐like formation promoting the extracellular bone matrix deposition and the expression of the osteogenic‐related proteins (alkaline phosphatase, osteopontin, collagen type‐1 and osteocalcin). Notably, when the hAFMSCs were co‐cultured in a 3D dynamic system with the hMCs, the presence of MK‐4 supported the cellular aggregate formation as well as the osteogenic function of hAFMSCs, but negatively affected the osteoclastogenic process. Taken together, our results demonstrate that MK‐4 supported the aggregate formation of hAFMSCs and increased the osteogenic functions. Specifically, our data could help to optimize bone regenerative medicine combining cell‐based approaches with MK‐4 treatment.